Penerapan Metode Pembelajaran Show and Tell Terhadap Keterampilan Berbicara Siswa Pada Pembelajaran Bahasa Indonesia di SD - Hisny Fajrussalam; -, Rifda Salma Azhary; Agus Muharam (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Life for people banded heavily on language. Humans always use language as a means of communication while interacting with others. Therefor, Indonesian language is made a required subject at all academic levels. One of the skills that must be mastered by students of the four language skills is speaking skills. This study was motivated by the low speaking skills of grade V students when participating in Indonesian language learning activities. This research was conducted at SDN 6 Sindangkasih with 18 research subjects. The purpose of this study is to improve learning activities so as to increase students' speaking activities and skills by using the Show and Tell learning method. The type of research used in this study is class action research. The results showed an increase in teacher activity, student activity, and student speaking skills. Cycle I the average acquisition of students' speaking skills amounted to 68,88 with the number of students who completed learning 10 people and students who did not complete learning 8 people. In cycle II, the average acquisition of students' speaking skills was 79,44 with the number of students who had completed learning 16 people and students who did not complete learning 2 people. With this, the application of the Show and Tell learning method is proven to be able to improve learning activities during the learning process so that it can improve students' speaking skills.